KINERJA PENYULUH PERTANIAN LAPANG DI BPP KECAMATAN PADEMAWU - Lia Kristiana; Fuad Hasan (Universitas Islam Madura, 2015)
Agricultural extension field is a valuable human resource, and is an integral part of a set of factors of production and the most important role than other factors in BPP Pademawu. There are 15 people in the field extension Pademawu BPP. Without a quality field agriculture Extension impossible a Pamekasan District Agriculture Office, especially in BPP Pademawu will succeed in achieving its objectives. Problems often arise in the management of human resources in an organization is a performance issue BPP Pademawu agricultural extension field and the methods used in counseling. This study aims to (1) Determine the approaches used in BPP Pademawu Extension in delivering agricultural extension, (2) to analyze the performance of Agricultural Extension at BPP Pademawu. Locations were selected intentionally (purposive), Consideration of site selection was based since the era of regional autonomy in the area of ​​institutional agricultural extension becomes less neglected. Respondents in this study is to involve as many as 15 respondents from extension workers and 112 respondents from farmers. The analytical methods used is descriptive qualitative. Based on the results of research on Performance Analysis of agricultural extension field in BPP Pademawu are as follows: 1) The technique Pademawu BPP approach used in agricultural extension based communication techniques include direct extension methods and extension methods indirectly. While based on the number of targets achieved include individual approaches a group approach and a mass approach. 2) Performance agricultural extension field in BPP Pademawu is high.